The Meaning of Gardening Activities among Older Adults with Chronic Illnesses: A Phenomenological Study on Quality of Life - Ellia Ariesti; Yafet Pradikatama Prihanto (Universitas Tribhuwana Tunggadewi, 2026)
Older adults with chronic illnesses often experience a decline in quality of life in physical, psychological, social, and spiritual aspects. Gardening is a non-pharmacological intervention that is easily accessible, holistic, and has the potential to improve the well-being of older adults. In addition to providing light physical exercise, gardening can also stimulate motor skills, provide a sense of calm, and strengthen social interactions. However, the meaning that older adults ascribe to gardening activities still requires further exploration. This study aimed to explain the meaning of gardening activities from the perspective of older adults with chronic illnesses. This research employed a qualitative approach using a phenomenological method. Participants were selected through purposive sampling, specifically older adults with chronic illnesses who actively engage in gardening activities at the Kenari 3 Community Health Post in Gunungronggo Village, Malang Regency. Data were collected through face-to-face, semi-structured interviews using an interview guide developed based on the study objectives. Data collection was halted after the 20th participant, as data saturation had been reached. Data were analyzed using thematic analysis with the assistance of NVivo, including coding, code comparison, diagram development, and theme generation. Data validity was ensured through time and participant triangulation. Nine themes emerged: tranquility while gardening, social interaction, gardening as work, positive feelings, family support, light exercise, enjoyment of nature, improved health, and gardening challenges. Gardening holds significant meaning for older adults with chronic illnesses. Beyond serving as a form of work, this activity provides a sense of calm, happiness, fulfillment of social needs, and helped relieve physical complaints. Gardening has the potential to be used as a non-pharmacological intervention that supports improved quality of life for older adults.